Descolonizar la historia de la tradición filosófica en Colombia: la necesidad de reevaluar los postulados historiográficos actuales (2020)
This article is a reflection on the progress and discussion trends of the history of the Colombian philosophical tradition and its historiographic presuppositions, and aims to contribute to the debate about the relevance of thinking about national philosophical traditions in the twenty-first century. Based on the valuation categories of the different intellectual products, it can be determined whether or not they are part of the national philosophical tradition. The concept of “philosophical normalization” is analyzed as an interpretative category of the Colombian tradition and, given its implications, its obsolescence is suggested with the aim of overcoming the reductionism, exclusion, and bias entailed by it. This article vindicates the nineteenth century attempts at social analysis and regional philosophical productions with the aim of contributing to a decolonial, broad, and unbiased reconstruction of the history of the Colombian philosophical tradition.